Measuring sustainable intensification in smallholder agroecosystems: A review - Smith, A.; Snapp, Sieglinde S.; Chikowo, Regis; Thorne, Peter J.; Bekunda, Mateete A.; Glover, Jerry (Elsevier, 2017)
Sustainable intensification (SI) is at the forefront of food security discussions as a means to meet the growing demand for agricultural production while conserving land and other resources. A broader definition of SI is emerging that takes into account the human condition, nutrition and social equity. Next steps require identification of indicators and associated metrics, to track progress, assess tradeoffs and identify synergies. Through a systematic, qualitative review of the literature we identified SI indicators, with a primary focus on African smallholder farming systems. We assessed indicators and metrics for which there is consensus, and those that remain contested. We conclude that, while numerous metrics for evaluating SI systems exist, many often-cited indicators lack strong sets of associated metrics.